Meneropong Praktik Nsionalisme Bernegara dalam Fiqih Kebangsaan - Khafidhotun Nasikhah; Jamaluddin (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The course of the history of the Unitary State of the Republic of Indonesia (NKRI) as a mu'ahadah wathaniyah (nation consensus) to knit togetherness in the midst of diversity based on Pancasila and the 1945 Constitution, its existence is always and continues to be tested. Geopolitical conditions are broadly changing and increasingly dynamic, the struggle for influence of superpowers, violence and civil war in the Middle East region has not stopped since the Arab Spring tragedy in 2010 until now. It will directly or indirectly affect national political conditions, with indications of efforts to import Middle Eastern conflicts into the country with the slogan Indonesia Bersyariat. This study aims to explore the practice of the state as an effort to explore religious nationalism in national fiqh. The nature of this research is from the library (library research), which consists of books, yellow books, al-Qur'an and al-Hadith. The data analysis technique used is descriptive qualitative data analysis technique with inductive method. The results of the research that has been done, it is known that nationalism and love for the homeland are concepts that have long been taught by the Prophet Muhammad. to guard, care for and defend their homeland from enemies (colonizers). The concept above teaches us the attitude of patriotism which in Islam has a fairly universal meaning, which is projected to protect religion and the state.